Petersberger Erklaerung: Anstoesse fuer eine zukunftsgerichtete Arbeitsmarktpolitik - Klaus F. Zimmermann; Michael C. Burda; Jürgen von Hagen; Kai A. Konrad; Friedrich G. Schneider; Gert G. Wagner (Institute for the Study of Labor (IZA), 1998)
n.a. – – In this paper six authors propose guidelines for German labor market policy, to overcome current discouragement and lead to a new balance of social security and individual competetiveness. Crucial aspects in this regard should be a reformed tax system based on excise instead of income taxes, and a system of incentives (vouchers) to encourage further education and individual initiative in the event of unemployment. In addition the declaration pleads for economic regulation of immigration and demands more marketability of honorary work. The welfare state should not be shattered but has to stimulate the individual to take economic risks and chances. This paper has been forwarded to a broader German public in order to influence discussion on the future course of labor market policy.
Keywords: J00; 330; labor market; migration and economics; tax system; welfare state